Determination of Temporal Change Land Use / Land Cover Using Remote Sensing and Geographic Information System Techniques the Central District of Samsun (1984-2011) - Orhan DENGİZ (Türkiye Tarımsal Araştırmalar Dergisi, 2014)
In our day natural resources fall short against endless human needs and increasing population. It is required for lands which are the leading natural resources to be used and planned according to natural environment potential. This study was conducted in Central district of Samsun province covered about 341 km2 and located between the latitudes 41° 25‟ 52”- 41° 12‟ 22” to 41° 42‟ 34” to north and longitudes 36° 09‟ 52”-36° 24‟ 31” east. Determination of land use efficiency of district selected for this study using satellite image and GIS was aimed. For this purpose the data of General Directorate of Rural Services which belongs to 1984 year, ASTER satellite images which belongs to 2005 and 2011 years and topographic maps were used. For performing calculations in ENVI 5.0v software unclassified classification applied and four main classes were formed. For determining the unclassified classes as classified the field work applied. The result of the classification forest, pasture, farm lands and non agricultural areas were determined as land use-land covers. For determining land use efficiency analog data were digitized and transferred to GIS database. Land use types and land use capability classes of 1984 year converted raster data by using GIS. Land use types of 1993, land use types of 2005 and 2011 and land use capability classes were compared. As the result of the comparison urbanization and unintended use increased in I., II. and III. class lands. In 1984 agricultural land has 24313.76 ha while, this amount decreased to 10120.96 ha in 2005 and 6960.69 ha in 2011. On the other hand, while non-agricultural area was 1893.36 in 1984, this area increased to 6301.66 ha in 2005 and 7917.73 ha in 2011. In addition, this study showed that to determine and to monitory for large areas‟ land cover and land use trend, remote sensing and geographic information system techniques have important role to generate accoriance and fast data.